Cardiopulmonary effects of ketamine-butorphanol-medetomidine and etorphine-azaperone drug combinations used to immobilise zebra (Equus zebra) - Zeiler, Gareth Edward (University of Pretoria, 2019)
Dissertation (MSc)--University of Pretoria, 2018.